Pandangan Ibnu Sina Terhadap Kondisi Jiwa Manusia dalam Buku Psikologi Islam (Panduan Memahami Kondisi Jiwa Manusia) - Solihatun Solihatun; Shohibul Adib (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
The thoughts of regarding the human soul make an important contribution to the treasury of Islamic knowledge, particularly in the fields of philosophy and psychology. The soul (nafs) is regarded as an immaterial substance that serves as the source of human consciousness, will, and life. In his philosophical framework, the soul has three main levels: the vegetative soul (al- nafs al-nabatiyyah), the sensitive soul (al-nafs al-hayawaniyyah), and the rational soul (al- nafs al-insaniyyah). The soul is a form (shurah) that cannot be seen with the naked eye. It is not a part of the human body; rather, the body serves merely as its dwelling place. The soul is eternal it does not perish even when the body ceases to exist. The soul and the body share a close relationship, and their connection forms a mutualistic symbiosis. The soul is defined as the primary perfection of the body; however, this does not mean that the soul precedes the body. Without the body, the soul cannot be considered a true soul. This research aims to explore in depth Ibnu Sina’s perspective on the condition of the human soul.